Effective Practices for Educators to Increase Online Interaction Quality - Razak , Ateerah Abdul; Razak, Amanina Abdul; Shukor , Farhana Haji (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2022)
Amidst the Covid-19 Pandemic is still with us, the teaching and learning process has undergone a revolution towards digital academia. Educators doubt whether large online classes are effective because virtual classrooms hinder good communication as learners do not interact meaningfully to class lectures. This study aims to examine the ways that self-efficacy can help to enhance online interaction in terms of student-content, student-student, student-teacher and student-medium and to investigate whether these interaction types are influential in the moderating effect of the perceived harm of getting COVID-19.This is a cross-sectional study which employs quantitative methods using a questionnaire that is designed based on the Social Capital Theory and consists of two domains. A sample of 641 learners who have experienced Online Distance Learning whether in secondary school, foundation, diploma, or degree programme reported their virtual learning experience. This study reveals that most of the participants agree that they obtained an effective online learning, nevertheless several issues related to a competent virtual learning needs to be solved such as the need to acknowledge students’ personality traits that are proactive could empower internet self-efficacy and online interaction quality. These research findings encourages for proactive interactions from all parties involved and the call for more relevant classroom activities and material that could ensure the success of virtual academia.